Tongue base schwannoma: a case report - Shendge, Neha Anand; Roy, Biswanath; Mukherjee, Subhrojyoti; Bose, Alokendu; Sutradhar, Arpita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Schwannoma is a benign, slow growing tumor which is most commonly seen in the VIII cranial nerve. Schwannoma was first described by Verocay in 1910. We have reported a case of a 52 year old female who presented to the hospital with complaints of difficulty swallowing, change of voice and a growth on the posterior one third of the tongue. Biopsy was done and sent for histopathological evaluation which confirmed the diagnosis of Schwannoma. She underwent Lip Split with Mandibulotomy surgery which was done with a awake fiberoptic nasal intubation followed by general anesthesia. The tumor was excised in toto. Her postoperative period was uneventful. Mandibulotomy with lip split provides more than adequate visualization of the masses on the posterior region of the tongue, allowing better maneuvering, ease and precise results for a skilled surgeon. Transoral approach may be the most widely used technique but the decision should be based on the clinical evaluation such as the size, shape and the anatomy of the patient. Narrowing down to the technique of choice should be done after a comprehensive evaluation of that patient. A team of various specialities like Otolaryngologist, Anaesthetist and radiologist is required for optimal execution for this surgery. To enhance our understanding a literature review between 2006 and 2023 was done which included the reports on tongue base schwannoma. A large number of them underwent transoral excision of the mass with a minority choosing mandibulotomy with lip split. A limited array of literature is available for tongue base schwannoma cases.